Idioms in the Series of “Gossip Girl Season 4”: Semantics Study - Taloko, Tiefanny Dewi Puspita (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2024)
The research focused on the idioms used in “Gossip Girl Season 4” after watching the phenomena of idiom use in this television series. This research aims to to identify the types of idioms and to explain the meaning of the idioms found in the series. This research used a qualitative descriptive method. This method is used to understand in detail the phenomenon of the research subject. The researcher seeks to reveal the underlying patterns, and meanings of the idioms within the series story through thorough analysis and interpretation. There are 47 idioms in the data, they are 18 transparent idioms, 27 semi-transparent idioms, and 2 semi-opaque idioms. The most frequent idiom in “Gossip Girls Season 4” belong to semi-transparent idiom. In order to fully comprehend the idiom, we must first understand the context: who is the speaker, what the speaker is talking about, when the speaker is speaking, and where the speaker is speaking.